A phenomenological approach on communication experiences between strength and conditioning coaches and head sport coaches - Charles, B. (Leadership Education Capstones, 2020)
This study investigates communication experiences between Strength and Conditioning Coaches and Head Sport Coaches usinga phenomenological approach. SixteenStrength and Conditioning Coaches were surveyed, via Qualtrics, to obtain basic demographics and answer open ended questions to understand communication experiences and strategies Strength and Conditioning Coaches use to have effective relationships, teamwork, and athletic performance with Head Sport Coaches. Participants were required to be currently working for a DI-DIII4-year Universityin the United States, have at least 1-year of Strength and Conditioning experience, an accredit certification related to training athletes at the college level, and be at least 21 years of age to be in the study. Triangulation was used through journal review andreview ofthe researcher`sjournal to compare the data in this study. Analysis of the open-ended questions, using a two-level coding system, and reviewing journals and researcher`s journal showed that Strength and Conditioning Coaches who communicate openly, frequently, and honestly with Head Sport Coaches achieved effective communication, relationships, teamwork, and athletic performance. Head Sport Coaches who provide autonomy, are collaborative, and set clear expectations will also assist in this endeavoras well as provide a greater experience for the Strength and Conditioning Coach. Scheduling, regarding competition and training sessions,appearedin the surveyto be a factorfor stress for Head Sport Coaches and Strength and Conditioning Coaches, which may affect exercise training programs.Strength and Conditioning Coaches should be flexible to adjust training programs accordingly as schedule changes or conflicts may arise. Consistently testing of key performance indicators of student-athlete`s wellness, performance, and health and sharing that information with Head Sport Coaches were found to be effective strategies to ensure student-athletes were performing at a high leveland reduce injuries. Face-to-face communication was found to be the favorite form of communication because it reduces confusion and interpretation from the Head Sport Coach.